Bridgeless Isolated Cuk PFC Implementation using PID and Neural Controller - R. Pireethi; R. Balamurugan (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The comparision of Bridgeless  Isolated Cuk converter using Proportional  Integral  Derivative (PID) and Neural controller (NC) is presented in this paper. Due to Diode Bridge Rectifier (DBR) conventional converters suffer from high conduction loss. Bridgeless Cuk converter is used  to eliminate the issues. Bridgeless   Isolated (BLI)  Cuk  converter is used to withstand high voltage. Compare to Continuous Conduction Mode (CCM) Discontinuous Conduction Mode (DCM) utilize less number of sensors. To obtain unity power factor it is used to  work in  DCM mode. BLI Cuk Converter is implemented in  two controller PID and  Neural controller to observe  power factor. Performance of BLDC motor  is simulated  by using MATLAB/SIMULINK software.